HIV medication adherence programs: the importance of social support. - Bontempi, Jean M Breny; Burleson, Laura; Lopez, Melissa Hofilena (Journal of community health nursing, 2004)
Since the advent of medical treatments for HIV, the promotion of adherence to these difficult treatment regimens has proven critical to disease management. Three Connecticut state-funded HIV medication adherence programs were evaluated.1 The purpose of this process evaluation was to explore and compare the goals and modality of each adherence program, assess client and staff satisfaction, and provide recommendations for the improvement of these programs. Focus group interviews with clients and individual interviews with staff were conducted at each of the programs. Interviews were transcribed, coded and analyzed with a code and retrieve method of theme identification. Focus group themes included the importance of social support on medication adherence and the "lifesaving" effect the program has had. The staff expressed that although complete adherence should be the long-term objective, more intermediate objectives should be considered (e.g., behavioral changes to increase clients' ability, self-esteem, and self-efficacy to take medications).
17 citations (Crossref) [2023-10-31] Place: United States Bontempi, Jean M Breny. Department of Public Health, Southern Connecticut State University, New Haven 06515, USA. brenybontej1@southernct.edu
Keywords: *Anti-HIV Agents/tu [Therapeutic Use]; *HIV Infections; *Health Promotion/og [Organization & Administration]; *Patient Compliance/px [Psychology]; *Social Support; Anti-HIV Agents; Attitude of Health Personnel; CD4 antigen; Connecticut; Female; Focus Groups; HIV Infections; HIV Infections/dt [Drug Therapy]; HIV Infections/px [Psychology]; Health Knowledge; Attitudes; Practice; Health Promotion; Human immunodeficiency virus infection; Humans; Male; Needs Assessment; Nursing Methodology Research; Organizational Objectives; Outcome and Process Assessment (Health Care); Outcome and Process Assessment; Health Care; Patient Compliance; Patient Education; Patient Education as Topic/og [Organization & Administration]; Program Evaluation; Questionnaires; Self Efficacy; Social Support; Surveys and Questionnaires; United States; antiretrovirus agent; article; attitude; behavior therapy; clinical article; controlled study; dept.pch; drug dose regimen; emotion; evaluation; female; health program; health promotion; human; interview; job satisfaction; male; outcomes research; patient compliance; patient education; professional practice; self concept; self esteem; self medication; social support; staff